(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article will address issues within the national culture – the struggle of true art with the product of cultural industry. We draw attention to the conflict in the Kazakh culture, when classical arts – serious, aesthetic cinema, intelligent literature, poetry clash with ubiquitous product media.Kazakh youth undergoes psychological treatment product of Western cultural industries, westernized minds are influenced in pursuit of profit, the ratings and meaning behind art forms are being lost. Such treatment fledgling young minds exposed through various channels of mass media. Firstly, in our opinion, the majority of Kazakhs middle and older generation are still experiencing an acute shortage of the meaning of life. Socio-economic crisis in our country in the 90s, accompanied by both a philosophical crisis of society and the individual. State of confusion, ambivalence, farewell to the past, with the old, outdated way of thinking, exacerbates the problem of spiritual values. In these circumstances, it seems to us, namely the existential communication practices are particularly important when the issues involved in «existential vacuum», as well as communication, which can help the single individual to get out of the state of frustration and overcome the crisis «secondary» socialization and identification. Key words: national culture, art, society, consciousness, conflict, mass media.